Perlindungan Hukum Atas Kawasan Lindung Gunung Klabat Kabupaten Minahasa Utara - Sinaga, Thor Bangsaradja; Tinangon, Edwin Neil; Pinasang, Bobby (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2025)
Concerns about environmental damage and destruction in the Mount Klabat conservation area in North Minahasa Regency have prompted this normative-juridical research to identify national legislation and regional regulations (perda) that can protect the area sustainably. The primary sources, including laws, presidential decrees, ministerial regulations, and regional regulations, were analyzed using a legislative, linguistic, and conceptual approach. It was concluded that synchronizing legal norms with regional regulations has ensured applicable laws for legal protection of the Mount Klabat area, even with clear regulations regarding the empowerment of indigenous communities within it. However, it is recommended that general and adaptive principles be developed for stronger synchronization and ease of legal implementation in the community, which requires further research involving multiple parties, including environmental law practitioners and academics.